2013
DOI: 10.1111/acem.12090
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of Emergency Department Patients' Knowledge, Beliefs, Attitudes, and Acceptance Toward Revised HIV Testing Strategies

Abstract: Objectives The objective of this study was to explore emergency department (EDs) patient’s knowledge, beliefs, attitudes, and acceptability towards revised human immunodeficiency virus (HIV) testing recommendations. Methods Participants were recruited in proportion to the racial, sex, and ethnic makeup of the study ED. Interviewers presented participants with a stimulus followed by questions about opt-out consent, elimination of separate written consent, and curtailed counseling. Three investigators coded al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Also, similar to results from our research group, Cowan et al importantly confirmed fundamental misunderstanding of opt‐out consent, which supports an existing notion that patients may not understand what they are consenting to . While the CDC explicitly states that “[s]creening should be voluntary and undertaken only with the patient's knowledge and understanding that HIV testing is planned,” these results, unfortunately, suggest otherwise.…”
Section: Misperception Negatively Affects Implementation Of Hiv Screesupporting
confidence: 87%
See 2 more Smart Citations
“…Also, similar to results from our research group, Cowan et al importantly confirmed fundamental misunderstanding of opt‐out consent, which supports an existing notion that patients may not understand what they are consenting to . While the CDC explicitly states that “[s]creening should be voluntary and undertaken only with the patient's knowledge and understanding that HIV testing is planned,” these results, unfortunately, suggest otherwise.…”
Section: Misperception Negatively Affects Implementation Of Hiv Screesupporting
confidence: 87%
“…The article by Cowan et al used semistructured interviews to assess patients' perceptions related to consent and counseling as suggested by the CDC . These authors nicely demonstrate support of the CDC recommendations for streamlining consent (i.e., integrating HIV consent into the general consent and eliminating the need for separate written consent); they also highlight differences in patients' perceptions related to counseling—some believing counseling is important and others not.…”
Section: Misperception Negatively Affects Implementation Of Hiv Screementioning
confidence: 95%
See 1 more Smart Citation
“…It is our belief, however, as well as others, that patients have a certain tolerance for testing and often don't expect explicit consent to have testing performed. 7 Additional study to support this assumption is warranted.…”
Section: Discussionmentioning
confidence: 98%
“…Of 34 patients, from varied backgrounds, polled at a public teaching hospital in New York about their understanding of, beliefs about and reaction to opt-out testing in the ED, [27] some lack of understanding of the option to opt out was found, but they were generally in favour, citing the potential health benefits as the main reason to support the opt-out process. The main confusion was that participants incorrectly assumed that they would face mandatory testing, rather than having the option to refuse, especially if not of decision-making capability.…”
Section: Hiv Testing In Lmicsmentioning
confidence: 99%